2018
DOI: 10.1177/2158244018805357
|View full text |Cite
|
Sign up to set email alerts
|

Badges and Bongs: Police Officers’ Attitudes Toward Drugs

Abstract: For unknown reasons, the research investigating police officers' attitudes toward drug use is underdeveloped. One study, by Wilson, Cullen, Latessa, and Wills, has directly investigated police officers' perceptions toward general vice crimes (including drug use) and perceived appropriate sanctions for committing these offenses. This article built upon that study. A survey measuring officers' attitudes toward drugs was developed and used to gather data from a large metropolitan police department in the South. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…In addition to the potential for increased stress, police behavior at these crime scenes could be influenced by their own assumptions about drugs, people who use drugs, and their children. Although the study of police perceptions of drugrelated crime is surprisingly limited, officers have been shown to support the implementation and enforce ment of stringent laws aimed at controlling the use, manufacture, and sale of all drugs (Jorgensen, 2018;Petrocelli et al, 2014). Research has shown that children tend to have more critical views of police than adults do (Brunson & Weitzer, 2009;Jesilow et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential for increased stress, police behavior at these crime scenes could be influenced by their own assumptions about drugs, people who use drugs, and their children. Although the study of police perceptions of drugrelated crime is surprisingly limited, officers have been shown to support the implementation and enforce ment of stringent laws aimed at controlling the use, manufacture, and sale of all drugs (Jorgensen, 2018;Petrocelli et al, 2014). Research has shown that children tend to have more critical views of police than adults do (Brunson & Weitzer, 2009;Jesilow et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, differences were found in the degree to which drug offences were deemed to be punishable, with more serious drug offences being rated as deserving harsher punishment [16]. In particular, the sale of drugs was viewed more harshly than personal use [15,17] and police officers took a more punitive approach towards drug sale than drug use [18]. Under Israeli law, cannabis is considered a dangerous substance and distribution of cannabis is considered drug trafficking, punishable by up to 20 years in prison.…”
Section: Drug Use and Social Perceptionmentioning
confidence: 99%
“…17 This study contributes to the underdeveloped literature investigating law enforcement officers' attitudes toward drug use and treatment. 4…”
Section: Study Backgroundmentioning
confidence: 99%
“…2 Community and governmental responses to SUDs have addressed them as public health and criminal justice matters. 3,4 While street-level enforcement strategies such as arrests have been the standard response toward illicit drug use, 5 public health responses address-ing prevention, treatment, and harm reduction have been popular in recent decades. These include screening, brief intervention and referral to treatment, 6 medication treatment, 7 and harm reduction approaches such as support programs, resources on safer ways to use substances, take-home naloxone kits, supervised consumption services, 8,9 and syringe exchange programs.…”
Section: Introductionmentioning
confidence: 99%